Higher serum levels of systemic inflammatory markers are linked to greater inspiratory muscle dysfunction in COPD. (10th March 2019) - Formiga, Magno F.; Vital, Isabel; Urdaneta, Gisel; Masters, Brett; Herrera, Julio; Campos, Michael A.; Cahalin, Lawrence P.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is associated with an inflammatory response that becomes more pronounced in acute exacerbations. Considerable attention has recently focused on the value of several inflammatory mediators in predicting worsening of COPD‐related symptoms. Whereas respiratory muscle dysfunction is also widely present in this population, little is known about how systemic inflammation relates to inspiratory muscle dysfunction in COPD. Methods: Fifty‐three males with mild‐to‐very severe airflow obstruction underwent blood sampling for 23 inflammatory markers, including acute‐phase proteins, cytokines and adipokines. Inspiratory muscle performance was assessed via the test of incremental respiratory endurance, providing measures of maximal (MIP) and sustained maximal (SMIP) inspiratory pressures. Results: The mean ± SD MIP and SMIP were 75.32 ± 19.62 cmH2 O and 406.15 ± 124.55 PTU. MIP negatively correlated with CRP, SAA and cystatin C ( r ‐values from −0.333 to −0.378, P < 0.02), while SMIP was inversely related to SAA and cystatin C ( r = −0.534 and r = −0.396, P = 0.00). Significant differences in CRP, SAA, cystatin C and PARC were also found between subjects with and without inspiratory muscle weakness. No additional significant relationships were observed between either MIP or SMIP and other inflammatory markers in the study. Conclusions: MIP and SMIP are markedly reduced with greater degrees of inflammation in COPD as expressed by higher levels of CRP, SAA and cystatin C. Future research is needed to further examine the above findings and determine the impact of systemic inflammation along with its underlying mechanisms on inspiratory muscle function in COPD.